2003
DOI: 10.1002/mrm.10596
|View full text |Cite
|
Sign up to set email alerts
|

Generalized diffusion tensor imaging and analytical relationships between diffusion tensor imaging and high angular resolution diffusion imaging

Abstract: A new method for mapping diffusivity profiles in tissue is presented. The Bloch-Torrey equation is modified to include a diffusion term with an arbitrary rank Cartesian tensor. This equation is solved to give the expression for the generalized Stejskal-Tanner formula quantifying diffusive attenuation in complicated geometries. This makes it possible to calculate the components of higher-rank tensors without using the computationally-difficult spherical harmonic transform. General theoretical relations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
398
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(400 citation statements)
references
References 24 publications
2
398
0
Order By: Relevance
“…The best way to convey these statistical features in terms of tissue characteristics such as cell density, type, or shape is currently an area of active investigation (Alexander et al, 2002;Clark et al, 2002;Frank, 2002;Liu et al, 2004;Maier et al, 2004a,b;Ozarslan and Mareci, 2003;Tuch et al, 2002Tuch et al, , 2003Zhan et al, 2003). An optimal diffusion model retains the full complement of structural information present in the data, but contains a minimal number of adjustable parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best way to convey these statistical features in terms of tissue characteristics such as cell density, type, or shape is currently an area of active investigation (Alexander et al, 2002;Clark et al, 2002;Frank, 2002;Liu et al, 2004;Maier et al, 2004a,b;Ozarslan and Mareci, 2003;Tuch et al, 2002Tuch et al, , 2003Zhan et al, 2003). An optimal diffusion model retains the full complement of structural information present in the data, but contains a minimal number of adjustable parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly adopted mathematical formalism used to express diffusion anisotropy in brain is the diffusion tensor imaging (DTI) model (Basser et al, 1994). Other expressions, such as a sum of diffusion tensors (Clark et al, 2002; Maier et al., 2004a,b), a spherical harmonic expansion of the diffusion profile (Alexander et al, 2002;Frank, 2002;Zhan et al, 2003), a function possessing higher moments than the DTI model function (e.g., kurtosis) (Liu et al, 2004;Ozarslan and Mareci, 2003), and methods for expressing diffusive displacement without reference to simplifying models (Tuch et al, 2002(Tuch et al, , 2003 have been proposed. We have found that water diffusion within fixed baboon brain may be modeled with high fidelity by selecting a single model from a series of expressions possessing varying degrees of radial symmetry on a voxel-by-voxel basis, provided that a constant term is added to the expression for the MR signal (see Appendix A).…”
Section: Introductionmentioning
confidence: 99%
“…The methods vary in their acquisition sampling and analysis approaches. High angular resolution diffusion imaging (HARDI) methods (including QBI: q-ball imaging; and GDTI: generalized DTI) typically obtain images with a constant moderate to high level of diffusion weighting (b > 1500 s/mm 2 ) over a large number (> 30) of non-collinear encoding directions (Liu et al, 2004;Özarslan and Mareci, 2003). The HARDI approaches may be used to detect and characterize regions of crossing white matter tracts; however, they are insufficient for characterizing aspects of non-monoexponential diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, whereas HARDI focuses on having a lot of samples on a single sphere, HYDI focuses on a better distribution of samples on the qspace. Very few methods have been proposed so far to take advantage of this kind of sampling: the generalized DTI (GDTI) method [28,29] is based on the Fick's diffusion law, and the DOT method [26,30] has been extended to multi-exponential radial decay. Nonetheless these methods use a larger set of data and are still based on prior models of the input signal radial behavior.…”
Section: Introductionmentioning
confidence: 99%